Uji Aktivitas Antiinflamasi Estrak Sirih Cina (Peperomia Pellusida) Pada Tikus Jantan Galur Wistar Yang Diinduksi Karagenan - Achmad Fauzi; Anita Dwi Septiarini; Tatiana Siska Wardani (Pusat Riset dan Inovasi Nasional, 2023)
Chinese betel plant (Peperomia pellucida), an herbal plant belonging to the Piperaceae family, Chinese betel plant (Peperomia pellucida). Research Stages: sample collection, extract preparation, extract standardization, determination of non-specific parameters, phytochemical screening, preparation of test solutions, anti-inflammatory activity tests, treatment of test animals. The results of maceration were filtered using filter paper, then the entire filtrate was concentrated using a vacuum evaporator and water bath at 60℃ to obtain a thick extract. The yield of 96% ethanol extract from Chinese betel powder (Peperomia pellucida) obtained was 4.531%. Based on the results, it has non-specific characteristics, namely drying shrinkage of 9.26%, ash content of 7.9% and water content of 4.15%. Phytochemical screening the compound tested was positive, A dose of 150 mg/kgBB is also an effective dose in inhibiting the formation of edema seen from the effect it gives is stable and has the highest percentage of edema inhibition compared to other doses, which is 34,35%.